2013
DOI: 10.3382/ps.2013-03051
|View full text |Cite
|
Sign up to set email alerts
|

The location of protoporphyrin in the eggshell of brown-shelled eggs

Abstract: Protoporphyrin has been identified as the main eggshell pigment in brown-shelled eggs. However, there has been some uncertainty concerning the distribution of the pigment within the shell (and cuticle) in brown-shelled eggs. Most previous studies have suggested that the bulk of the shell pigment is deposited in the cuticle of the shell. The present study measured the levels of protoporphyrin in intact eggshells and in shells from which the cuticle had been removed, using eggs from flocks at 3 different ages. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
2
40
1
Order By: Relevance
“…This indicated that hens lay small eggs with a darker eggshell colour but lay large eggs that are lighter coloured. These results were supported by similar studies by Odabasi et al (2007), Flock et al (2007), Cavero et al (2010), Cavero et al (2012), Lukanov et al (2015) and Samiullah and Roberts (2013). As a result of these selection studies on these newly developed breeding lines, shell colour will also be considered as a factor in the shell index values.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This indicated that hens lay small eggs with a darker eggshell colour but lay large eggs that are lighter coloured. These results were supported by similar studies by Odabasi et al (2007), Flock et al (2007), Cavero et al (2010), Cavero et al (2012), Lukanov et al (2015) and Samiullah and Roberts (2013). As a result of these selection studies on these newly developed breeding lines, shell colour will also be considered as a factor in the shell index values.…”
Section: Discussionsupporting
confidence: 78%
“…Research by Aygun (2013) stated that moulting stress has been shown to severely affect eggshell colour once the hen resumes laying, with the extent of the response differing among individual hens. A study by Samiullah and Roberts (2013) researched 33-, 50-and 67-week-old HyLine Brown hens to determine the amount of protoporphyrin IX in the eggshells. The amount of protoporphyrin IX in 1 g of whole eggshell was not significantly different, but in the cuticle itself, was found to be significantly higher in eggs from 50-week hens as compared with the 33-and 67-week hens.…”
Section: Discussionmentioning
confidence: 99%
“…The L* measurements represent the intensity of brown eggshell colour; the higher the value, the lighter the colour of the eggshell. Egg weight was measured using an analytical balance, and the eggs were further processed for protoporphyrin IX (PP IX) quantification following the method of Samiullah and Roberts 15 . The post-oviposition times (time-points) were 2, 5, 15 and 23.5 hrs for the four groups of hens selected.…”
Section: Methodsmentioning
confidence: 99%
“…Standard dilutions (0 to 6.87 nMoles) prepared from protoporphyrin IX di-sodium salt (Sigma Aldrich, Australia) were read at the same wavelength in order to construct a standard curve for the calculations of the amount of PP IX per gram of tissue. The quantification of PP IX in the eggshells was performed according to Samiullah and Roberts 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation